Nuel Belnap on Indeterminism and Free Action - Müller, Thomas (Springer Nature, 2014)
In this introduction to the Outstanding contributions to logic volume devoted to Nuel Belnap's work on indeterminism and free action, we provide a brief overview of some of the formal frameworks and methods involved in Belnap's work on these topics: theories of branching histories, specifically "branching time" and "branching space-times", the stit ("seeing to it that") logic of agency, and case-intensional first order logic. We also draw some connections to the contributions included in this volume. Abstracts of these contributions are included as an appendix. Nuel Belnap's work in logic and in philosophy spans a period of over half a century. During this time, he has followed a number of different research lines, most of them over a period of many years or decades, and often in close collaboration with other researchers:1 relevance logic, a long term project starting from a collaboration with Alan Anderson dating back to the late 1950s and continued with Robert Meyer and Michael Dunn into the 1990s; the logic of questions, developed with Thomas Steel in the 1960s and 1970s; display logic in the 1980s and 1990s; the revision theory of truth, with Anil Gupta, in the 1990s; and a long-term, continuing interest in indeterminism and free action. This book is devoted to Belnap's work on the latter two topics. In this introduction, we provide a brief overview of some of the formal frameworks and methods involved in thatwork, and we drawsome connections to the contributions included in this volume. Abstracts of these contributions are presented in Appendix A.